2022
DOI: 10.1186/s13098-022-00839-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of a panel of urine biomarkers of kidney disease in two paediatric cohorts with Type 1 diabetes mellitus of differing duration

Abstract: Background The pathogenesis of diabetic kidney disease (DKD) is complex and involves both glomerular and tubular dysfunction. A global assessment of kidney function is necessary to stage DKD, a progressive kidney disease that is likely to begin in childhood. The present study evaluated whether kidney injury biomarkers identified as early DKD biomarkers in adults have any prognostic value in the very early stages of childhood diabetes. Methods We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It would also be interesting to research their correlation with other parameters, including disease stage and antibody levels. In addition to CTSS, our serum proteomics analysis revealed 69 other potential biomarkers that could also be further investigated, since it was shown that for some diseases they can be described through biomarker panels, not only one biomarker [89]. For the development of a suitable panel, our candidates identified in this study are available in PRIDE [90].…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to research their correlation with other parameters, including disease stage and antibody levels. In addition to CTSS, our serum proteomics analysis revealed 69 other potential biomarkers that could also be further investigated, since it was shown that for some diseases they can be described through biomarker panels, not only one biomarker [89]. For the development of a suitable panel, our candidates identified in this study are available in PRIDE [90].…”
Section: Discussionmentioning
confidence: 99%